การใช้สิทธิในทรัพย์สินทางปัญญาเป็นหลักประกันหนี้ - สุชาดา กรรณสูต (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
Whether intellectual property rights can be used as securities for the performance of an obligation under the laws on mortgage and pledge must be considered if intellectual property rights are regarded as property under the Civil and Commercial Code (The "Code") and whether they are recognized by the law on secured transactions as security and subject to execution. According to the doctrine of security law, the mortgaged property must be immovable property and special movable property and, for the pledge, the delivery to the grantee of movable property is the material element. This research concludes that intellectual property rights are property under the Code because they correspond to the meaning of property therein. Nevertheless, intellectual property rights are not immovable property which can be used as security in term of mortgage and cannot be delivered in term of pledge. In addition, the procedure of execution of intangible property as security is still vague under the applicable law. Although under the general principles of lawson juristic act, and contract the parties could agree to use intellectual property rights as security, hardly used in practice. This thesis proposes two alternatives for using intellectual property rights as security. The first one is to amend the provisions of the pledge of rights under the Code to cover the pledge of property rights beyond immovable property rights with the registration of such pledge and to amend the provisions of the intellectual property laws in parallel with the Code amendment. The second recommendation is to enact a specific law regarding the use of intellectual property rights as security. Both methods make the creditor become grantee the secured creditor and preferred creditor, and in the same time, aim to safeguard the third party s interest from encumbranced property by providing the registration system which discloses the details of the previous transactions relating to the intellectual property rights. Furthermore, the grantor still has beneficial interest in his property. If the proceeds are less than the amount due, the debtor of the obligation remains liable for the difference. Last of all, the research also recommends the amendment of the Civil Procedure Code to clarify the execution of intellectual property rights as securities. A number of drafted statutory provisions under the above mentioned concepts are also proposed herein.